(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Attendance monitoring is an important aspect of classroom management because it helps teachers maintain accurate student records and monitor participation. However, traditional attendance methods, such as manual roll calls and paper-based records, are often time-consuming and prone to human error. This study developed ClassScan, a smart classroom identification scanner designed to automate attendance monitoring using Radio Frequency Identification (RFID) technology. The system was developed using an ESP32 microcontroller, RFID scanner, OLED display, DS3231 Real-Time Clock module, Micro SD Card module, and ESP32-CAM. A developmental research design was employed to develop and evaluate the system. Six teacher-participants assessed the usability, effectiveness, and operational performance of the prototype through a structured evaluation questionnaire. The findings revealed that the system obtained an overall mean score of 4.48, interpreted as "Strongly Agree," indicating a high level of user acceptance. Participants reported positive perceptions regarding the system's ease of use, attendance-recording capability, and operational performance during testing. The findings suggest that ClassScan demonstrates potential as a practical attendance-monitoring solution within a localized educational setting. Further studies involving larger samples and more comprehensive validation procedures are recommended.